2019
DOI: 10.1111/1440-1681.13120
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits high glucose‐induced mesangial cell proliferation, inflammation and ECM expression through the SIRT1‐FOXO1‐autophagy axis

Abstract: The aim of this study was to investigate the role of metformin in high glucose‐induced mesangial cell proliferation, inflammation and extracellular matrix (ECM) accumulation and to elucidate the underlying mechanism of metformin function. An MTT assay was used to examine rat mesangial cell (RMC) proliferation. The levels of TNF‐α, IL‐6 and TGF‐β in RMCs were determined by ELISA. The protein expression of fibronectin, collagen IV and autophagy‐related proteins (Beclin‐1, LC3‐I and LC3‐II) in RMCs was detected u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…FOXO1 can reduce the damage of oxygen free radicals to kidneys by inducing autophagy . Our previous studies have shown that metformin could induce Sirt1‐FoxO1 autophagy signal axis, up‐regulate autophagy level, and inhibit cell proliferation, extracellular matrix and inflammatory factor secretion in glomerular mesangial cells induced by high glucose …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FOXO1 can reduce the damage of oxygen free radicals to kidneys by inducing autophagy . Our previous studies have shown that metformin could induce Sirt1‐FoxO1 autophagy signal axis, up‐regulate autophagy level, and inhibit cell proliferation, extracellular matrix and inflammatory factor secretion in glomerular mesangial cells induced by high glucose …”
Section: Introductionmentioning
confidence: 99%
“…12 Our previous studies have shown that metformin could induce Sirt1-FoxO1 autophagy signal axis, up-regulate autophagy level, and inhibit cell proliferation, extracellular matrix and inflammatory factor secretion in glomerular mesangial cells induced by high glucose. 13 In this study, we used a high-fat diet combined with streptozotocin (STZ) to establish diabetic rat model, and observed whether metformin exerted renal protective effect by regulating autophagy mediated by the Sirt11-FoxO1 signalling pathway in DN rats.…”
mentioning
confidence: 99%
“… 32 The activation of autophagy was reported to induce the suppression of cell proliferation, migration, and ECM accumulation. 33 , 34 In the previous study, the reduced autophagic capacity of fibroblasts was associated with the pathogenesis of HS. 35 Then, the authors also investigated the influence of ANGPT2 knockdown on HSF autophagy.…”
Section: Discussionmentioning
confidence: 91%
“…On the contrary, FoxO1 is also related to the expression of genes, which seems to be important for the protection from cell death due to oxidative stress. Increased activity of FoxO1 by SIRT1 deacetylation apparently reduces the effect of diabetic nephropathy by autophagy (Xu et al, 2019(Xu et al, , 2020.…”
Section: Regulation Of Foxo1 Activity Through Post-translational Modificationmentioning
confidence: 99%
“…For example, metformin itself is a very common diabetes drug to improve insulin resistance conditions (Giannarelli et al, 2003). Metformin promotes the activation of FoxO1 via activation of AMPK, promoting deacetylation by SIRT1 or inhibition mTOR kinase (both mTORC1 and mTORC2) which in turn also inhibits Akt to promote longevity of cells and relieve oxidative stress (Kalender et al, 2010;Ren, Shao, et al, 2020;Wang et al, 2018;Xu et al, 2019Xu et al, , 2020Zhou et al, 2001). Inhibition of Akt phosphorylation is also shown by shikonin derivative DMAKO-05 (Yang et al, 2016).…”
Section: Foxo1 Activitiesmentioning
confidence: 99%